A New Approach to Global Stability of Discrete Lotka-Volterra Predator-Prey Models. (1st June 2015) - Kim, Young-Hee; Choo, Sangmok
Abstract : An Euler difference scheme for a three-dimensional predator-prey model is considered and we introduce a new approach to show the global stability of the scheme. For this purpose, we partition the three-dimensional space and calculate the sign of the rate change of population of species in each partitioned region. Our method is independent of dimension and then can be applicable to other dimensional discrete models. Numerical examples are presented to verify the results in this paper.